The influence of women’s earning status and other socioeconomic factors on their healthcare-seeking behavior: evidence from the Bangladesh household income and expenditure survey, 2016 / Dr. Shahnaz Haque and Prof. Dr. Saidatulakmal Mohd - Haque, Shahnaz; Mohd, Saidatulakmal (Universiti Teknologi MARA, Kedah, 2025)
Economic progress is intricately tied to the concept of human capital. The active participation of women who earn income plays a significant role in mitigating poverty and addressing gender disparities. Consequently, in the pursuit of fostering sustainable economic development, a comprehensive exploration of women's health concerns becomes imperative. The acquisition of accessible and qualified medical care stands as a vital component in preserving overall well-being. Regrettably, women residing in numerous underdeveloped nations often neglect this fundamental necessity. Improving healthcare-seeking behavior (HSB) is considered a vital strategy to optimize the utilization of healthcare services. However, women in the majority of developing countries demonstrate inadequate healthcare-seeking behavior (HSB). This study seeks to evaluate the influence of women's earning status and other socioeconomic factors on their HSB, using data from the Bangladesh Household Income and Expenditure Survey (HIES) 2016. Here we considered those women who were ill and sought any type of treatment during the 30 days of the survey. Based on Andersen’s behavioral model of health services use, this study employed a multinomial logistic regression model. The findings indicate that while women's educational attainment, urban residence, and chronic illness elevate the likelihood of seeking qualified healthcare providers, women who have income are more inclined to seek treatment from a pharmacy/traditional/self-care. These findings underscore the necessity for initiatives aimed at improving the HSB among women who have income and those residing in rural areas.